Bacteriological Profile of Chronic Suppurative Otitis Media in Patients at a Tertiary Level Hospital - Kumar, Dhirendra; -, Priyadarshini; Agarwal, M K; Prakash, P (Eastern Journal of Medical Sciences, 2016)
Background: Chronic suppurative otitis media (CSOM) is a disease of multiple etiologies and is well known for its persistence and recurrence in spite of antimicrobial treatment often leading to complications. Hence, knowledge of the current bacterial pathogens along with susceptibility pattern is important in management of cases with CSOM. Objectives: The aim of present study was to observe the bacteriological profile of CSOM and their antimicrobial susceptibility pattern. Methods: The 142 samples of ear discharge from 100 patients of CSOM, reported to the out-patient department of Otolaryngology, S.S. Hospital, Banaras Hindu University, Varanasi between July 2012 and June 2013 were collected processed for Gram stain and culture isolation. Results: On culture isolation, Staphylococcus aureus was the commonest pathogen, followed by Pseudomonas spp., Proteus spp., and Escherichia coli. Staphylococcus aureus showed maximum susceptibility towards Clindamycin whereas leading gram negative isolate Pseudomonas aeruginosa showed maximum susceptibility towards levofloxacin. Conclusion: The study proved to be useful for clinicians in management of CSOM. Further, there is a definite need to ponder over those 14% cases which were negative on aerobic culture.